Bird count - Edwards Richmond, Susan (Peachtree Publishing Company Inc., 2019)
An excited young girl and her mother carefully participate in the Christmas Bird Count as part of a team of citizen scientists, tallying birds found in different habitats near their home. Includes facts about birding and why the Christmas Bird Count is important.